Family Dysfunction and Its Impact on the Al-Qur’an Learning Process of Children in Pontianak City (A Study of QS. At-Tahrim Verse 6) - Darma Ranti, Utin; Chanigia, Gabriel Angel; Jabbar, Luqman Abdul (Jurnal Ilmiah WUNY, 2026)
Background: The weakening role of the family in children's Al-Qur'an education has become a growing concern, particularly in Pontianak City, where dependence on Al-Qur'an Education Centers (TPA) and private Quran tutors is increasing. The home has not fully functioned as the primary space for Qur'anic learning, and parental involvement in mentoring and reinforcing religious values remains limited, potentially leading to dysfunction in the family's role in children's religious education. Objectives: This study aims to analyze the role of parents in Al-Qur'an education and to examine the impact of family dysfunction on children's Al-Qur'an learning in non-formal educational institutions. Method: A qualitative approach with field research methods was employed. Data were collected through observation and in-depth interviews with purposively selected TPA teachers and private Quran tutors in Pontianak City, West Kalimantan, and analyzed thematically using Talcott Parsons' structural functionalism framework through the A-G-I-L scheme. Result: Parents' low Al-Qur'an literacy, insufficient learning supervision at home, and weak reinforcement of Qur'anic values in daily life contribute to children's low motivation, discipline, and learning continuity. Conclusion: The success of children's Al-Qur'an education is highly determined by strengthening the parental role as primary educators through adaptation, goal attainment, role integration, and the continuous maintenance of Qur'anic values within the family.